SA cardiovascular laboratories mining diverse, yet relevant research topics - Woodiwiss, Angela; Norton, Gavin (SA Heart Journal, 2017)
This issue of SA Heart reports on some ongoing work performed in South Africa that engages with more fundamental issues of the mechanisms of cardiovascular disease. This special edition of the journal highlights some of the high quality, internationally competitive, clinically relevant, basic cardiovascular science presently being undertaken by a number of groups around the country in this regard. Although the topics covered in the present issue are diverse, all have an important clinical context and in this editorial we will attempt to describe this context.